About the (Not)obvious Relationships of Religion, Religiousness, Spirituality and Human Health - Zalewska-Meler, Agnieszka (Paedagogia Christiana, 2025)
Among the categories that elude unambiguous definitions and measurements, the concepts of religion, religiosity, spirituality and health are located. The aim of the analyses presented in the text is to reconstruct the ways of understanding them, in order to indicate mutual relations in the context of phenomenographic research. This approach made it possible to reach the content of the consciousness of the respondents through the prism of their experiences and the meanings attributed to them. The first part of the text outlines the research problem and justifies the choice of phenomenographic research. The second part presents the theoretical foundation of the categories of religion, religiosity and spirituality in contemporary scientific discourse, which was the basis for defining in the third part how they function in the subjective perception of the respondents and their relations with health. Based on the map of network dependencies, it was established that: 1) religion is an entity external to a human being, the presence of which in the lives of the respondents is based on the search for the truth about human nature, 2) not so much religion, but the personal dimension of religiosity and religious and non-religious spirituality become a source of new meanings in the face of negative circumstances in the biographies of the respondents, i.e. recovery, i.e. coping with illness (recovery) and strengthening in everyday functioning, i.e. acquiring proficiency in making decisions that serve the quality of life conditioned by the state of health (empowerment).